The complete Peanuts. 1963 to 1964 - Schulz, Charles M. (Charles Monroe), 1922-2000 (Fantagraphics Books ; Distributed to the book trade by W.W. Norton, 2007)
Collects all the "Peanuts" comic strips as originally published in newspapers, including both daily and Sunday strips.